2018
DOI: 10.1159/000495720
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Protects Dopaminergic Neurons Against MPP+-Induced Oxidative Stress and Regulates the Endogenous Anti-Oxidant System Through ERK

Abstract: Background/Aims: Many clinical studies have demonstrated that statins, especially simvastatin, can decrease the incidence of Parkinson’s disease (PD). However, the specific underlying mechanism remains unclear. This study aimed to investigate how simvastatin affects experimental parkinsonian models via the regulation of extracellular signal-regulated kinase 1/2 (ERK1/2)-mediated activation of the anti-oxidant system. Methods: l-Methyl-4-phenylpyridine ion (MPP+)-treated SH-SY5Y cells and substantia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…TTP overexpression reduced apoptosis induced by MPP + (Figure 5D,E) and promoted cell survival ( Figure 5A,C). Similar to previous observations, 34 cleaved-caspase-3 was induced by MPP+ and TTP knockdown and decreased by TTP overexpression (Figure 5G,H). Besides, Bcl2 protein was reduced by MPP + in MN9D cells, and si-TTP further reduced the Bcl2 expression ( Figure 5G), whereas TTP overexpression promoted the Bcl2 expression ( Figure 5H).…”
Section: Mpp + Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…TTP overexpression reduced apoptosis induced by MPP + (Figure 5D,E) and promoted cell survival ( Figure 5A,C). Similar to previous observations, 34 cleaved-caspase-3 was induced by MPP+ and TTP knockdown and decreased by TTP overexpression (Figure 5G,H). Besides, Bcl2 protein was reduced by MPP + in MN9D cells, and si-TTP further reduced the Bcl2 expression ( Figure 5G), whereas TTP overexpression promoted the Bcl2 expression ( Figure 5H).…”
Section: Mpp + Modelsupporting
confidence: 91%
“…Besides, many studies confirm enhanced NOX2 expression in the MPP+/MPTP/6‐OHDA model. ROS generation in MPP + ‐treated DA neurons is NOX2‐dependent 5,34 . The reduction of NOX2 expression in PINK1 knockdown SH‐SY5Y cells significantly attenuates ROS production 61 .…”
Section: Discussionmentioning
confidence: 98%
“…The cells were fed every 2-3 days and sub-cultured once they reached 80-90% confluence. Primary neurons were conducted as previously described [25]. Newborn C57BL/6J mice were obtained within 24 h of birth from HFK Bioscience Co., Ltd. (Beijing, China).…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Statins are inhibitors of HMG-CoA reductase -the ratelimiting enzyme in cholesterol biosynthesis -but they have also exhibited neuroprotective properties, particularly in terms of the CNS-penetrant statin, simvastatin (Tong et al, 2018;Yan et al, 2018;Mattii et al, 2019;Simchovitz et al, 2019;Hanan et al, 2020;reviewed in Carroll and Wyse, 2017). It was also recently suggested that simvastatin treatment can reduce the risk of developing progressive supranuclear palsy and potentially delaying onset of symptoms (Bayram et al, 2020).…”
Section: Simvastatinmentioning
confidence: 99%